Karakterisasi Bakteri Rhizosfer Putri Malu (Mimosa pudica) yang Berpotensi sebagai Dekomposer dalam Pembuatan Biourin - Febriyantiningrum, Kuntum; Sriwulan, Sriwulan; Nurfitria, Nia (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
This research aims to determine the characterization of the rhizosphere bacteria of the roots of Mimosa pudica in its contribution as a decomposer agent that will be used in making of biourine. The research held in June-August 2023, was carried out in several stages, like the preparation stage, the bacterial isolation stage, and observing the macroscopic and microscopic characteristics of the bacteria. The results of the macroscopic and microscopic characteristics obtained during the observations showed that the isolates in the MOL of the roots of Mimosa pudica resembled the characteristics of bacteria from the genera Bacillus (MAP6), Rhizobium (MAP4), Pseudomonas (MAP1, MAP2, MAP3, MAP5, and MAP8), and Klebsiella (MAP7). These four genera are types of soil bacteria that are capable of producing plant hormones that can speed up the process of nutrients absorption and breakdown of organic material in the soil optimally.